Towards an understanding of the effectiveness of advertising - Corkindale, David (Cranfield University, 1976)
The author has been concerned with a study of "The Measurement of Advertising Effectiveness" since 1972. . During the course of this study, some 11 reports have been produced. In accor- dance with Regulation 14.9 of CIT's Regulations governing the submission of material for higher degrees, these reports are submitted, together with an exposition of the material contained within them. The exposition which is presented here attempts to describe the contents of the reports in the overall context of the study of which they were a part. Hence, -this exposition contains: a description of the study; a description of the overall methodology employed; a summary of the contents of the reports; and, an appraisal of the study's methods and outputs. No precedent exists for such expositions and the author has chosen the form and content which he believes will best. allow the contents of the reports to be appreciated.